STUDENTS TRAINING TENDENCY IN THE EU AND UKRAINE: LEGAL ASPECT - Mospan, Natalia (The Modern Higher Education Review, 2017)
The article presents the current trends in the preparation of students in higher education in the EU and Ukraine. These trends are identified on the basis of the analysis of legal documents (legal acts of primary and secondary law), which reflect the EU response to contemporary global changes in education: globalization and marketization. These processes require from higher education to provide new approaches to the training of students in accordance with labour market demands. The new Law on Higher Education in Ukraine directs the development of national higher education system to integration into the European Higher Education Area. The new law establishes financial principles of higher education system, creates conditions for strengthening cooperation of government agencies and businesses with universities on the principles of autonomy of higher educational institutions. An important goal is to prepare competitive human capital for national high-tech innovation and development, to provide the labour market with skilled workers. The author considers that the legal documents of the EU and Ukraine try to reflect the current trends in training of students in accordance with the processes of globalization and marketization in education.